Effects of complex coastal topography on overland tsunami flows - Kok, Xue Yuan (2014)
The main goal of this project was to examine the effects of various experimental parameters on the behaviour of tsunami waves inside and outside coastal structures such as tunnels during a tsunami event, as well as to analyse the fluctuations in air pressure inside these tunnel-like structures when impacted by tsunami waves. Solitary waves were used to simulate the tsunami waves while a Perspex model comprising a cliff and straight tunnel were introduced to represent both a natural geological formation and a man-made structure that are likely to be found in actual coastal areas. To determine the extent to which some of the key experimental parameters affected the wave height of the tsunami waves, a series of carefully crafted experimental runs was conducted incorporating several variations in each of the parameters. The parameters in question were namely the water depth, incident wave height and the distance of the cliff from the shoreline. In addition, changes in the air pressure within the tunnel were examined by introducing a screw at the top of the tunnel and examining its effect on the air pressure when it was both present and absent. Based on the experimental data, it was found that both the water depth and incident wave height shared a positive correlation with the actual wave height measured but the distance from the shoreline was inversely proportional to the wave height. Where the air pressure was concerned, the pressure recorded in the presence of the screw was significantly higher than when the screw was removed. These findings provide a clearer idea of the key factors that could have an effect on tsunami waves and the resulting damage suffered. Moving forward, this project can be expanded to include detailed investigations of the effects of both the slope and relative wave height on the wave run-up phenomenon, as well as the calculation and prediction of tsunami waves on coastal structures. The effect of the run-up height on the inundation distance can also be explored, since the inundation distance of tsunami waves have a direct impact on the amount of damage suffered at coastal sites.